CD4 Count and anti Retroviral Therapy for HIV Positive Patients with Cancer in Nigeria -A Pilot Study - Atara I. Ntekim; Ayo M. Folasire (Clinical Medicine Insights: Oncology, 2010)
Background Highly Active Anti Retroviral Treatment (HAART) improves the outcome of HIV positive patients treated for cancer. In our center HAART is only commenced in HIV positive patients with malignancy if the CD4 T lymphocyte count is less than 200 cells/ul. Presently, the outcome of treatment in these patients is poor. Objective To evaluate the influence of CD4 T- cell count and HAART on treatment outcome of HIV positive patients with cancer managed at the oncology service of The University College Hospital, Ibadan- South West Nigeria. Patients and Methods Twenty two adult HIV positive patients with malignancies who presented for treatment at our hospital from 2007 to 2009 were closely monitored by the investigators. Relevant clinical data collected included age, sex, HIV status, type of malignancy, CD4 counts, history of ART, ECOG performance status, prescribed oncology treatment with regularity of treatment and to follow up conditions. Results Twenty two patients aged between 26 and 67 years were evaluated. The performance status of all patients was at least ECOG 2. Three ART naive patients with initial CD4 counts 450 cells/ul and above were able to complete oncology treatment without HAART with good malignant disease control. Five other patients on HAART before the diagnosis of malignancy with CD4 counts 350 cells/ul and above were also able to complete their treatments on schedule with good outcome. Eight HAART naive patients with initial CD4 counts less than 370 cells/ul had inconsistent treatments with poor outcome. Conclusion Based on these observations, we propose that HAART should be commenced on all HIV positive patients diagnosed with malignancy with an initial CD4 count less than 450 cells/ul in our environment. Further studies in low resource settings with appropriate sample sizes are however needed to validate these findings.